Preventing mass violence : a whole community approach - Warnick, Mark S. (Wiley, 2024)
"In the last decade there has been a steady and unnatural increase in the amount of mass violence perpetrated in the United States. This disturbing trend of mass violence has been seen in schools, businesses, festivals, malls, and other crowded areas. Most often this mass violence is a mass shooting event. Some attribute this increase in mass violence to the Contagion Effect (a theoretical explanation related to the media), while others blame guns, mental health, and a whole host of other issues. Law enforcement does their best to prevent these senseless mass shootings, domestic terrorist attacks, and international terrorist attacks, but they rarely receive critically needed intelligence from the local community in time to prevent these acts. Law enforcement agencies more often than not struggle to receive credible intelligence prior to an attack. If they do receive intelligence, in most instances they rarely have sufficient manpower to properly investigate this intelligence fully. If they do receive intelligence, in most instances they rarely have sufficient manpower to properly investigate this intelligence fully, or they become stuck in how to charge someone who has not committed a crime. Furthermore, after an incident we often hear about the odd behaviors that were seen before the attack, which were never reported. By utilizing a whole community approach, these warning signs can be recognized and reported, reducing the risk they will remain unnoticed prior to an act of mass violence"-- Provided by publisher.
Keywords: Violence -- Prevention.; Police-community relations.; Violence.; elektronické knihy; electronic books